Advancing non-destructive sex determination on human dental enamel using Raman spectroscopy - Raphael Hug; Anna E. Wood; Frank J. Rühli; Patrick E. Eppenberger (Scientific Reports)
Abstract Biological sex determination is essential for analyzing human skeletal remains in archaeology, anthropology, and forensic science. This study investigates whether Raman spectroscopy of intact human dental enamel can be used as a non-destructive method for sex estimation. Orthogonal partial least squares discriminant analysis (OPLS-DA) and logistic regression identified sex-specific spectral characteristics in 88 human teeth from 47 modern individuals (26 females, 21 males). The OPLS-DA model showed excellent performance, with R2Y(cum) = 0.943 and Q2Y(cum) = 0.895. Raman shift wavenumbers at 373, 1182, and 1600 cm−1 were identified as the most reliable discriminators and included in a final logistic regression model. This model achieved an area under the receiver operating characteristic curve (ROC-AUC) of 0.98, a sensitivity of 0.87, and a specificity of 0.94. Our results indicate that Raman spectroscopy can effectively differentiate male and female human dental enamel based on subtle differences in molecular composition—possibly linked to residual differences between AMELX and AMELY-derived proteins. This non-destructive, rapid, and reliable method offers a valuable alternative for sex determination in contexts where chemical analysis is impractical or sample preservation is critical and holds promise for future applications in archaeological and forensic material.